Peningkatan Pengetahuan Ibu-Ibu PKK Desa Papahan, Kecamatan Tasikmadu Mengenai Stunting - Liss Dyah Dewi Arini; Saryadi Saryadi; Anton Susanto; Musta’in Musta’in (Compromise Journal Community Proffesional Service Journal, 2025)
Mother is a leader in a family who is tasked with managing the nutritional needs of toddlers. Knowledge about the nutritional needs of toddlers and stunting among PKK mothers in Papahan Village, Tasikmadu is still limited, because many of them come from underprivileged families and have low educational backgrounds so that basic knowledge from the family is not optimal (less attention). This community service activity aims to provide understanding to PKK mothers to know the nutritional needs of toddlers and provide counseling to PKK mothers about stunting. The counseling method is carried out using the lecture method and explanations about the nutritional needs of toddlers and prevention of stunting with posters and power points. The results of this community service activity are that PKK mothers understand the nutritional needs of toddlers and the prevention of stunting. The conclusion of this community service activity is that PKK mothers can know the nutritional needs of toddlers and the prevention of stunting.